1986
DOI: 10.1346/ccmn.1986.0340311
|View full text |Cite
|
Sign up to set email alerts
|

57Fe Mössbauer Spectroscopy of Montmorillonites: A New Interpretation

Abstract: Abstract--The 57Fe M6ssbauer spectra of several montmorillonites, measured at room temperature and 453 K, showed a considerably broadened Fe 3+ resonance which can be computer-fitted with a similarly broadened Fe 3+ doublet. In some spectra, particularly if all linewidths were constrained to be equal, this broadened Fe 3 § resonance was further resolved into overlapping inner and outer Fe 3+ doublets, also having broad linewidths. In accordance with recent electron diffraction evidence, the assignment by previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 12 publications
2
37
0
Order By: Relevance
“…The linewidth for the inner octahedral Fe 3+ doublet (0.18 mm/s) is rather narrow and is considered to be .~ an artifact of computer-fitting a minor component to the experimental resonance of a disordered structure . The linewidth for the outer octahedral Fe 3+ doublet (0.48 mm/s) is broader .~ than those observed by Cardile and Johnston (1985) -~ for nontronites (0.32 mm/s), but similar in magnitude to those for montmorillonites (Cardile and Johnston, 1986). The broader linewidth serves to indicate that vermiculite and montmorillonite have a similar degree -o of structural disorder resulting from the presence of other octahedral cations (e.g., A13+, Mg~ § These nearest and next-nearest neighbor cations give variety to the type and arrangement of ions about each octahedral = t~ Fe 3 § site and so broaden the octahedral Fe 3+ doublets.…”
Section: Untreated Vermiculitementioning
confidence: 47%
See 2 more Smart Citations
“…The linewidth for the inner octahedral Fe 3+ doublet (0.18 mm/s) is rather narrow and is considered to be .~ an artifact of computer-fitting a minor component to the experimental resonance of a disordered structure . The linewidth for the outer octahedral Fe 3+ doublet (0.48 mm/s) is broader .~ than those observed by Cardile and Johnston (1985) -~ for nontronites (0.32 mm/s), but similar in magnitude to those for montmorillonites (Cardile and Johnston, 1986). The broader linewidth serves to indicate that vermiculite and montmorillonite have a similar degree -o of structural disorder resulting from the presence of other octahedral cations (e.g., A13+, Mg~ § These nearest and next-nearest neighbor cations give variety to the type and arrangement of ions about each octahedral = t~ Fe 3 § site and so broaden the octahedral Fe 3+ doublets.…”
Section: Untreated Vermiculitementioning
confidence: 47%
“…Johnston and Cardile (1985) and Cardile and Johnston ~, (1985), however, showed that nontronite has two nonequivalent cis-octahedral sites. Furthermore, for lowFe montmorillonites, Cardile and Johnston (1986) .z showed that, in accord with electron diffraction evidence (Tsipursky and Drits, 1984), the Fe 3 § is located essentially in the trans-octahedral sites for some sampies. As a result of the relatively low iron levels in montmorillonites considerable variation exists in the arrangements of nearest and more distant neighboring cations.…”
Section: Untreated Vermiculitementioning
confidence: 65%
See 1 more Smart Citation
“…On the basis of their iron content, illites and glauconites are intermediate between montmorillonite, which generally has a low iron content, and nontronite, which has a higher iron content. Recently, Johnston and Cardile (1985) and Cardile and Johnston (1985) carried out a systematic Mrssbauer spectroscopic study of nontronites having different iron contents and interlayer cations and a number of montmorillonites (Cardile and Johnston, 1986). As a continuation of this work the results of a similar M/Sssbauer study of an iron-rich montmorillonite, an illite, and a glauconite are presented here, and the patterns of iron substitution in these phyllosilicates are discussed.…”
Section: Introductionmentioning
confidence: 87%
“…The dominant octahedral cation in nontronites and ferruginous smectite is Fe; and in some nontronites Fe occupies a fraction of the tetrahedral sites (Goodman et al 1976, Cardile 1987, 1989, Cardile and Johnston 1985, 1986, Luca 1991, Luca and Cardile 1989. It is the only major element in the smectite structure that potentially may exist in two relatively stable oxidation states, Fe(II) and Fe(III), and a change in its oxidation state in situ alters the physical and chemical properties of the clay (Stucki 1988, and references therein, Komade1 et al 1990, Stucki and Tessier 1991, Khaled and Stucki 1991, Gates et al 1993.…”
Section: Introductionmentioning
confidence: 99%